The Effect of The Active Learning Strategy Type Everyone is Teacher Here on The Improvement of The Speaking Skills in Five Grade Elementary School: Pengaruh Strategi Active Learning Tipe Everyone Is Teacher Here (Eth) Terhadap Keterampilan Berbicara Siswa Sd Kelas V - Windi Widiasmara; Kemil Wachidah (Academia Open, 2022)
The purpose of this study was to determine whether there was an effect of the Active Learning Strategy Type Everyone Is Teacher Here on improving the speaking skills of elementary school students in Grade V at SDN Kwedenkembar Mojokerto, the purpose of conducting research at SDN Kwedenkembar was because students at the SDN had very poor speaking skills. In the learning process, students only speak occasionally because there are reasons of fear and lack of confidence and make their speaking skills lacking. This research was conducted using a quantitative approach using True Experimental Design research with Posttest Only Control Design. There are two groups in this design, namely the Experiment class and the Control class. The results of this study indicate that there is an effect of Active Learning Strategy Type Everyone Is Teacher Here on improving the speaking skills of fifth grade elementary school students at SDN Kwedenkembar Mojokerto.